Pendampingan Pembelajaran Membaca AlQuran Menggunakan Metode Tartil di Taman Pendidikan Quran Jamiatul Muksinin - Olivia, Olivia; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2023)
The tartil method is considered a practical and fast Alquran learning method to help students read the Alquran well. The aim of this assistance is to provide learning pedagogy for teaching staff at TPQ Jamiatul Muksisnin in accordance with the methods applied, and to provide supporting facilities for teaching staff at TPQ Jamiatul Muksisnin. The service partners are all students at TPQ Jamiatul Muksisnin. The method used in this assistance is through a Participatory Action Research (PAR) approach oriented towards community empowerment where this assistance is carried out to solve problems that exist in the community, precisely at TPQ Jamiatul Muksinin, by applying learning through the tartil method it can provide satisfaction and increasing students' ability to read the Koran. The results of this assistance show that students are very enthusiastic and enjoy this activity because it brings other benefits in training their Alquran reading skills. It can be seen that students are able to understand the tartil method so they can read the Alquran well, correctly and fluently. These results also show that the tartil method can improve students' ability to read the Alquran precisely and accurately.